2019
DOI: 10.3390/ijms20184362
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Epitope Prediction Using Peptide Sequence Descriptors and Machine Learning

Abstract: In this work, we improved a previous model used for the prediction of proteomes as new B-cell epitopes in vaccine design. The predicted epitope activity of a queried peptide is based on its sequence, a known reference epitope sequence under specific experimental conditions. The peptide sequences were transformed into molecular descriptors of sequence recurrence networks and were mixed under experimental conditions. The new models were generated using 709,100 instances of pair descriptors for query and referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This strategy limits the number of candidates from large peptide libraries by predicting and ranking their biological activities from sequences, so-called Quantitative Structure–Activity/Property Relationship (QSA/PR) studies. Successful QSA/PR applications include the discovery of novel antimicrobial peptides 10 13 or epitopes 14 and, the design of anticancer peptides 15 – 17 . Besides to the predictive power of QSA/PR methods, it is essential to consider their limitations, which lie into those of supervised learning.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy limits the number of candidates from large peptide libraries by predicting and ranking their biological activities from sequences, so-called Quantitative Structure–Activity/Property Relationship (QSA/PR) studies. Successful QSA/PR applications include the discovery of novel antimicrobial peptides 10 13 or epitopes 14 and, the design of anticancer peptides 15 – 17 . Besides to the predictive power of QSA/PR methods, it is essential to consider their limitations, which lie into those of supervised learning.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analysis showed that the reference epitope activity and perturbation of the Shannon entropies were the more important descriptors. The model introduced by the authors is expected to have an impact in the in silico screening of peptides, and contribute to the field of vaccine design by taking advantage of the epitope prediction and the established structure–activity relationships [ 129 ].…”
Section: Selection Of Nanomaterials Tailored For Improvements In Qual...mentioning
confidence: 99%